17th October: Proper 24 - Clark-King, Ellen (The expository times, 2010)
The article presents a recommended sermon for the 17th of October 2010. It focuses on Pentecost 21 and suggests that God is present in every human experience. It cites several passages in the Bible including verses 27-34 of chapter 31 of the book of Jeremiah, verse 14 of chapter three and verse five of chapter four of the book of Timothy and verses 1-8 of chapter 18 of the book of Luke. The author explains the real life applications of the passages mentioned in the sermon.